Governance and Implementation of Lecturer Human Resources Development Policies in Private Universities - Zet Abdullah; Supriyatno (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study examines the implementation of human resource (HR) development policies and governance frameworks for lecturers at the Palembang College of Psychology (STIPSI) through the lens of Government Science. Lecturer HR development is a key aspect of public policy in higher education, with its effectiveness shaped by both implementation and the quality of institutional governance. The research employs a qualitative, descriptive-analytical approach, utilizing in-depth interviews, systematic observations, and document analysis. Policy implementation is assessed using George C. Edward III’s framework—communication, resources, disposition, and bureaucratic structure—while governance is evaluated based on good governance principles. Findings indicate that HR development policies are supported by a normative framework and leadership commitment, but are not fully institutionalized at the systemic level. Effectiveness is limited by resource constraints, incomplete procedures, and primarily consultative participation. The hierarchical governance structure, centered on a foundational entity, influences resource allocation and decision-making. The study concludes that policy implementation and governance are mutually reinforcing in determining the quality of lecturer HR development. Theoretically, it offers a comprehensive governance framework for private higher education. Practically, it recommends strengthening procedures, implementing performance-based evaluations, and enhancing substantive participation to ensure sustainable HR development.